Interrogative utterances in spoken Lithuanian: quantitative aspects of investigation - Balčiūnienė, Ingrida; Simonavičienė, Laura (Lietuvių kalba, 2009)
The paper introduces the results of an investigation into spoken Lithuanian based on the Corpus of Spoken Lithuanian and carried out in Vytautas Magnus University. In the course of investigation the interrogative utterances used in spontaneous language were classified according to function and structure. The quantitative analysis of the data accessed from the Corpus of Spoken Lithuanian was based on a special computer program CHILDES. The results have shown that spoken Lithuanian gives preference to closed interrogative utterances rather than open interrogative utterances. Closed interrogative utterances in most cases use no interrogative particles; utterances with interrogative particles are much less frequent. In the latter subgroup interrogative particles mostly occur in the utterance-initial (e.g. ar, gal etc.) rather than utterance-final position (e.g. taip, ne, ane etc.). In the class of open interrogative utterances adverbial modifier utterances prevail; in the latter subclass interrogative utterances of the adverbial modifier of place dominate.